A influência do uso das tecnologias de informação e comunicação nos espaços domésticos contemporâneos: uma abordagem em Maceió, Alagoas - Duarte, Alana Tenório Carnaúba Guimarães (2016)
In the face of changes experienced by emerging ways of life through the use of Information and Communication Technologies (ICT), especially after the mobility achieved through wireless network (wi-fi), this work aimed to investigate the occurrence of physical changes in domestic spaces from these existing communication processes. The research was based on a bibliographic study on lifestyle and home environments, in the application of an online questionnaire with a portion of the population of the city of Maceio and analysis of the spaces offered by the local housing market made for a family "standard ". The daily activities were modified and one of the factors that happened was the addition of virtual spaces in the physical home environments, making hybrid and changing the whole dynamics of home use. As a result, it was observed that the invariance of residential typologies does not take into account the real needs of the residents, but not prevent them from using their electronic devices on considered traditional spaces, as it is also in these virtual spaces, that part of everyday life effective. Thus, it was found that the division of the house into three sectors (social, intimate and service) initiated by bourgeois society and consolidated during the twentieth century, has been dissolved, much the appropriation of spaces by residents, than what has been offered by the housing market.